A Comparative study between the two interferon gamma releasing assays in the diagnosis of pulmonary tuberculosis - Asmaa Z. Al- Ghreer; Zainalabdeen A. Abdualla (Tikrit Journal of Pure Science)
Objectives: To examine  and compare the diagnostic value of Interferon gamma releasing assay (IGRAs) (T- SPOT TB and Qunati FERON Gold in Tube) in the diagnosis of pulmonary tuberculosis.